Pengaruh PDRB terhadap Pajak Daerah Dan Pendapatan Asli Daerah (PAD) Kota Denpasar - Marliyanti, Dwi Sundi; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 6, Juni 2014 (pp.227 - 281), 2014)
Denpasar is the capital city of Bali Province which has grown into a metropolis . To improve capabilities in the areas of funding for the activities of their own regions , both for governance and for public services , the government tried to increase revenue through local taxes . One of the factors that affect revenue source is the growth of GDP . The purpose of this study was to determine the direct effect on GDP and PAD strip Tax , Local Tax direct influence on PAD , and Indirect Effects of GDP to PAD Denpasar through the Regional Tax . The data used in this study is a secondary data sourced from BPS Denpasar , which is then analyzed with path analysis method. Results showed GDP directly affects the Local Taxes and PAD Denpasar , Local Tax directly affect PAD Denpasar , and indirectly affect the GDP of the Regional Tax revenue through Denpasar .
Keywords: GDP , Local TaxesandLocal Revenue